Factors associated with depression among heart failure patients at selected public hospitals in Addis Ababa, Ethiopia: A cross sectional study. - Kassahun Alemayehu; Yohannes Ayalew Bekele; Teshome Habte Wurjine (Public Library of Science (PLoS), 2022)
This study aimed to Assess Factors associated with depression among heart failure patients at cardiac follow-up clinics in a government teaching hospital of Addis Ababa. A cross-sectional study design was employed to assess Factors associated with depression among 424 heart failure patients at selected public hospitals of Addis Ababa who were selected by using a systematic random sampling method from January 1 to 30, 2021 at four public hospitals. Sample was proportionally allocated for each study hospital and then data were collected by using structured-interview questionnaires. Bivariate and Multivariate logistic regression analysis was done to examine the possible predictors and variables with the statistical association of P-value of < 0.05 and a 95% confidence interval were considered. Data were gathered from heart failure patients in cardiac follow clinic with 100% response rate. Among the 424 respondents [mean age: 52.7 (SD) 17.5 years; 56.1% women], prevalence of depression was 56.1%. Among the 424 respondents [mean age: 52.7 (SD) 17.5 years; 56.1% women], prevalence of depression was 56.1%. New York Heart Association class III and IV was highly associated with depression respectively. Furthermore, poor self-care behaviours alcohol use, poor social support, poor knowledge level, were associated with depression and statistically significant. The findings from this study showed that depression is highly prevalent among heart failure patients and age of respondent, alcohol intake, self-care behaviour, social support, knowledge level, and co-morbidity were independently associated with depression. Therefore, all institutions of cardiac centre should work on screening for depression in heart failure patients, and consult psychiatrists and psychologists for early detection and measures.